Elektronik haberleşme alanında idarenin düzenleme, denetleme ve yaptırım yetkisi - Özelçi, Mustafa Aytaç (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Hukuk Anabilim Dalı / Kamu Hukuku Bilim Dalı, 2012)
Elektriksel işaretlere dönüştürülebilen her türlü işaret, sembol, ses, görüntü ve verinin kablo, telsiz, optik, elektrik, manyetik, elektromanyetik, elektrokimyasal, elektromekanik ve diğer iletim sistemleri vasıtasıyla iletilmesi, gönderilmesi ve alınması olarak tanımlanan elektronik haberleşme, 2008 yılında yürürlüğe giren Elektronik Haberleşme Kanunu ile düzenlenmiştir. Bu Yasa ile elektronik haberleşme hizmetleri kamu hizmeti anlayışıyla özel hukuk kişilerince üstlenilmiştir. Bu bağlamda anılan Yasada özel hukuk kişilerinin yetkilendirilmesi, bildirim yoluyla yetkilendirme ve kullanım hakkı yoluyla yetkilendirme biçiminde iki şekilde gerçekleşmektedir.
The regulation, supervision and sanction authority of administration in the electronic communication sector
Electronic communications are the transmission, exchange and receiving of all kinds of signals, symbols, sounds, images and data which could be converted into electrical signals, by means of cable, radio, optic, electric, magnetic, electromagnetic, electrochemical, electromechanical and other types of transmission systems. Authorization is the registration of entities providing electronic communications services and/or electronic communications network in the eye of the Authority and pursuant to such registration, or granting of certain rights and obligations specific to electronic communications services to these entities. Authorization for the installation and operation of any kind of electronic communications equipments, systems and networks; assignment of the necessary frequencies, numbers, satellite positions and associated resources and the arrangement thereof are under the State?s terms of reference. When companies who have notified the Authority do not need the assignment of resources such as number, frequency and satellite position for electronic communications services and/or electronic communications network or infrastructure which they plan to provide and/or to operate; they shall be authorized pursuant to the notification to the Authority. In case they need assignment of resources they shall be authorized upon receiving the right of use from Information and Communication Technologies Board.
Keywords: Denetim; Control; Düzenleme; Arrangement; Elektronik; Electronics; Elektronik Haberleşme Hukuku; Electronic Communication Law; Yaptırımlar; Sanctions; Özel Hukuk; Private Law; İdari denetim; Administrative supervisions; İdari yaptırımlar; Administrative sanctions; İletişim; Communication